2011
DOI: 10.1016/j.molcel.2011.09.020
|View full text |Cite
|
Sign up to set email alerts
|

Live Cell Imaging of Telomerase RNA Dynamics Reveals Cell Cycle-Dependent Clustering of Telomerase at Elongating Telomeres

Abstract: The telomerase, which is composed of both protein and RNA, maintains genome stability by replenishing telomeric repeats at the ends of chromosomes. Here, we use live-cell imaging to follow yeast telomerase RNA dynamics and recruitment to telomeres in single cells. Tracking of single telomerase particles revealed a diffusive behavior and transient association with telomeres in G1 and G2 phases of the cell cycle. Interestingly, concurrent with telomere elongation in late S phase, a subset of telomerase enzyme cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
106
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 105 publications
(111 citation statements)
references
References 35 publications
5
106
0
Order By: Relevance
“…Disruption of the Tlc1 -Ku80 interaction reduces telomere length while not eliciting an est1 phenotype. When assessing telomere association of telomerase by live-cell imaging, it seemed that the Tlc1 -Ku80 interaction might only promote a transient interaction with telomeres, whereas the stable interaction in late S phase is mediated by Cdc13 -Est1 (Gallardo et al 2011). The Ku-mediated stimulation of telomerase may also involve its role in nuclear accumulation of Tlc1, which is reduced in Kudeficient cells (Gallardo et al 2008;Pfingsten et al 2012).…”
Section: Telomere Replicationmentioning
confidence: 99%
“…Disruption of the Tlc1 -Ku80 interaction reduces telomere length while not eliciting an est1 phenotype. When assessing telomere association of telomerase by live-cell imaging, it seemed that the Tlc1 -Ku80 interaction might only promote a transient interaction with telomeres, whereas the stable interaction in late S phase is mediated by Cdc13 -Est1 (Gallardo et al 2011). The Ku-mediated stimulation of telomerase may also involve its role in nuclear accumulation of Tlc1, which is reduced in Kudeficient cells (Gallardo et al 2008;Pfingsten et al 2012).…”
Section: Telomere Replicationmentioning
confidence: 99%
“…The results presented reconcile the telomere/telomerase association models, providing an integrated view of how telomere homeostasis is achieved. 16 Live Cell Imaging of TLC1 RNA…”
Section: Telomerase In the Act: United We Standmentioning
confidence: 99%
“…[18][19][20] We recently adopted it to produce a version of TLC1 bearing ten MS2 stem loops near the 3' end of the mature RNA. 16 Co-expression of this tagged TLC1-10xMS2 RNA with the MS2 coat protein fused to GFP yielded in several fluorescent foci in yeast nuclei (named hereafter TLC1-GFP). FISH experiments directed against TLC1 RNA confirmed that the position of the TLC1-GFP fluorescent foci correspond to the absolute position of the TLC1 RNA.…”
Section: Dynamics In Yeastmentioning
confidence: 99%
See 2 more Smart Citations